Catholic theological ethics in the world church the plenary papers from the first cross-cultural conference on Catholic theological ethics - Keenan, James F. (Theology and religious studies / Agnes M. Brazal, series editor, 2008)
"A compilation of the plenary papers at the First Cross-cultural Conference on Catholic Theological Ethics in Padua, Italy. The panelists from five continents sought to answer the following questions: What are our moral challenges; how are we responding; and what hope do we have for the future?"--Publisher's description.